Evaluating the efficacy and safety of antidepressants in patients with bipolar disorder. Issue 10 (3rd October 2019) - Cheniaux, Elie; Nardi, Antonio E.
ABSTRACT: Introduction : The use of antidepressants (AD) in the treatment of bipolar depression is one of the most controversial issues in psychopharmacology. For some, AD are useful, but, for others, they should never be used in bipolar depression. Areas covered : This review examines published clinical studies on the use of ADs in bipolar depression, addressing their clinical efficacy and the occurrence of side effects, manic switches, cycle acceleration, and suicidal behavior. Meta-analyzes and review articles on the subject are also discussed. Expert opinion : Approved therapeutic options for bipolar depression are associated with not very high response rates and a high incidence of adverse effects. Patients with bipolar depression present very heterogeneous responses to the use of ADs. Some improve significantly, while others, especially those with concomitant manic symptoms, have had previous episodes of treatment-emergent mania or are rapid cyclers, exhibit manic switches or cycle acceleration. The authors conclude that the real question is not whether ADs should or should not be used in bipolar depression, but which patients benefit from these drugs and which ones are impaired. The concept of bipolar spectrum and a dimensional approach on bipolar/unipolar distinction may be useful for understanding the heterogeneity of responses to ADs.